Get rid of pancreatic cancer by inhibiting garbage disposal?: Comment on “UAE1 Inhibition mediates the unfolded protein response, DNA damage and caspase-dependent cell death in pancreatic cancer” by Rehemtulla et al - Geismann, Claudia (Transl Oncol, 2020)
• stress pathways including the ER stress, the proteasome and the unfolded protein response (UPR) are increasingly reported to be suitable targets in PDAC; • UAE1 is the most abundant of two ubiquitin activating enzymes (UAE) regulating the initial step of the ER stress associated protein degradation (ERAD) pathway; • The group of Rehemtulla elegantly showed that TAK-243, a small molecule inhibitor of Ubiquitin activating enzyme 1 (UAE1) nduced apoptosis in PDAC cells and a subcutaneous mouse model of the disease; • In other preclinical models of cancer, especially in lymphatic malignancies, this compound showed promising results in directly inducing apoptosis but also in increasing the response to other conventional cytotoxic therapeutic approaches; • Strikingly, these effects were also reported in cells resistant to drugs that target other protein degradation pathways, like proteasome inhibitors, indicating divergent molecular mechanisms.